Les fleuves dans l'œuvre romanesque de Jean-Marie Gustave Le Clézio - Westerlund, Fredrik (Université de Helsinki, 2011)
Abstract: The rivers in Jean-Marie Gustave Le Clézio's fiction.
Keywords: Le Clézio, J. M. G; kirjallisuudentutkimus; ranskankielinen kirjallisuus; joet; symboliikka; litteraturvetenskap; litteratur på franska; floder, åar och älvar; symbolik